Quality of life and academic performance of University of the Free State first-year Health Sciences students - Mostert, Arnelle (University of the Free State, 2019)
An in-depth study was carried out to investigate the quality of life of first-year health sciences students and to determine the correlation between quality of life and academic performance. The results of this study could be used to address challenges related to quality of life and academic performance in the Faculty of Health Sciences at the University of the Free State (UFS) in South Africa. A few studies have been performed internationally (outside South Africa) to evaluate quality of life in certain health sciences (mainly medical and nursing) students. A direct relationship between the quality of life and academic performance of preclinical medical students (first three study years) was found in a study performed in Saudi Arabia. First-year students, in general, are a population that faces physical health, psychological and social challenges, which are caused by the transition from high school to university learning, and these students need to learn how to balance academic workload and their personal lives. No studies have been done at the Faculty of Health Sciences at the UFS to investigate the quality of life of first-year health sciences students using the WHOQOL-BREF questionnaire. A few studies have been conducted outside South Africa to evaluate differences in the quality of life of students who reside in either on-campus or off-campus accommodation, but not at the Faculty of Health Sciences at the UFS. The problem that was addressed by this study is the lack of information regarding the quality of life of first-year students enrolled in the Faculty of Health Sciences at the UFS. Diverse quality of life factors may impact their academic performance. The aim of the study was to measure quality of life by means of the WHOQOL-BREF questionnaire and to determine the correlation of quality of life scores with the academic performance of UFS first-year health sciences students. This research study conducted a quantitative descriptive cross-sectional design. A survey was used to collect the data by means of a questionnaire. The research methods comprised a literature study, completion of the WHOQOL-BREF questionnaire, as well as gathering demographic and academic performance information about the respondents. The quality of life of students in the various health sciences disciplines, who reside in either on-campus and off-campus residences, was measured and the correlation between their quality of life and academic performance was determined. The study revealed that the overall quality of life and health of students at the Faculty of Health Sciences, UFS, was good. The quality of life domain score order varied in the schools and academic programmes of the Faculty of Health Sciences, for on-campus and off-campus students and students who had lived in either urban or non-urban (rural) areas before attending university. The 10 most prominent facets of the four quality of life domains were the following: sleep and rest; energy and fatigue; work capacity; thinking, learning, memory and concentration; negative feelings; bodily image and appearance; sexual activity; freedom, physical safety and security; participation in and opportunities for recreation/leisure activities and physical environment. The findings of the study could make a valuable contribution to the knowledge base about the quality of life of first-year health sciences students, and could assist the researcher and other health care professionals to address challenges related to students’ quality of life and academic performance.
Dissertation (M.HPE. (Health Professions Education))--University of the Free State, 2019
Keywords: Quality of life; Academic performance; First-year students; Residences (on campus, off campus); South Africa; Health sciences students (medical, nursing, physiotherapy, occupational therapy, optometry, dietetics)